ETIKA DALAM PELAKSANAAN KONSELING ONLINE DITINJAU DARI KODE ETIK ABKIN - Purnamasari, Yuniarti; Budiman, Nandang; Nadhiroh, Nadia Aulia (Universitas PGRI Semarang, 2024)
The increasing need for online counseling has influenced counselors to be competent in carrying out online counseling. However, in practice there are still obstacles and limitations, so guidelines are needed as a reference for implementing online counseling. This study aims to find out how the ethics in implementing online counseling are viewed from the ABKIN code of ethics. The method used in writing this research is Systematic Literature Review. The research data comes from journal articles that are relevant to the research topic obtained from Google Scholar and the ABKIN Code of Ethics Book. The result of this research is that there is an ethical issue of online counseling, in order to obtain ethical development in the application of online counseling in terms of the ABKIN Code of Ethics.